Negotiation of identities: the case of aeta ambala’s media engagement - Viray, Kriztine Rosales; Viray, Joseph Reylan B (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research explores the impact of media engagement on the identity perceptions of the Aeta Ambala, an indigenous group in the Philippines, particularly after the 1991 Mt. Pinatubo eruption. This catastrophic event led to significant displacement and cultural shifts for the Aeta, who were forced to adapt to urban lifestyles. The study focuses on the differences in identity perceptions between the older and younger generations, with the former holding onto pre-eruption cultural norms and the latter aligning more with urban and resettlement community cultures. Employing in-depth interviews and focus group discussions, the study finds that media representations often negatively portray the Aeta Ambala, leading to discrimination and altering self-perception. Despite this, the community maintains a strong sense of ethnic identity, viewing it as an immutable aspect of their heritage. Media engagement is seen as inevitable for staying informed, particularly in emergencies, but it also influences perceptions of the outside world and reshapes cultural and ethnic identity. Younger generations, more engaged with media, tend to adopt external beauty standards and lifestyles, leading to early marriages and cultural indifference. There is also a noted mistrust towards media organizations due to exploitation concerns. In conclusion, the study highlights the complex relationship between media interaction and self-identification within the Aeta Ambala community, suggesting that while media engagement alters perceptions and behaviors, the core Aeta Ambala culture remains strong and resilient.